Clinical governance for ostomates at risk of peristomal skin complications. (12th September 2019) - White, Pamela; Evans, Moira
Abstract : This clinical study focuses on peristomal skin complications (PSCs). For many patients, the causative factor behind peristomal moisture-associated skin damage was contact dermatitis caused by effluent leakage, resulting in sore and excoriated skin. PSCs are costly to the patient in relation to pain, time and worry and also impact nursing activity levels and healthcare costs. The study identifies the number of patients presenting with PSC, the causative factors and their resolution using medical grade Manuka honey flanges.